$\begin{cases}4x-3y=19\\2x+3y=11\\\end{cases}$
`<=>` $\begin{cases}4x-3y=19\\4x+6y=22\\\end{cases}$
`<=>` $\begin{cases}4x-3y=19\\9y=3\\\end{cases}$
`<=>` $\begin{cases}y=\dfrac13\\x=\dfrac{3y+19}{4}=5\\\end{cases}$
Vậy `(x,y)=(5,1/3)`
\(\left\{{}\begin{matrix}4x-3y=19\\2x+3y=11\end{matrix}\right.\)⇔\(\left\{{}\begin{matrix}6x=30\\2x+3y=11\end{matrix}\right.\)
⇔\(\left\{{}\begin{matrix}x=5\\10+3y=11\end{matrix}\right.\)⇔\(\left\{{}\begin{matrix}x=5\\y=\dfrac{1}{3}\end{matrix}\right.\)
vậy...
\(\left\{{}\begin{matrix}4x-3y=19\\2x+3y=11\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}6x=30\\2x+3y=11\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=5\\2.5+3y=11\end{matrix}\right.\\ \Leftrightarrow\left\{{}\begin{matrix}x=5\\10+3y=11\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=5\\3y=1\end{matrix}\right.\Leftrightarrow\left\{{}\begin{matrix}x=5\\y=\dfrac{1}{3}\end{matrix}\right.\)
Vậy (x;y)=\(\left(5;\dfrac{1}{3}\right)\)